1996
DOI: 10.1097/00004836-199606000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange for Dramatic Gestational Hyperlipidemic Pancreatitis

Abstract: We describe the response to plasma exchange in a woman with extreme gestational hyperlipidemia and severe pancreatitis. Her serum triglyceride reached an astounding level of 21,300 mg/dl-among the highest concentrations ever recorded. Two consecutive plasma exchanges led to a remarkable reduction in triglyceride levels of 73% and 82%, respectively. Plasma viscosity decreased by 50% after the first plasma exchange. This was associated with an equally dramatic and unexpectedly rapid resolution of severe pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Hormonal changes in pregnancy predispose to increased triglyceride levels, but only patients with genetic abnormalities in lipoprotein metabolism are prone to severe gestational hypertiglyceridemia [7]. In most cases of gestational hypertriglyceridemia reported in the literature, TPE was not initiated in the absence of pancreatitis [4][5][6][7][8][9] despite the established association of pancreatitis with life-threatening fetal complications and increased maternal mortality [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal changes in pregnancy predispose to increased triglyceride levels, but only patients with genetic abnormalities in lipoprotein metabolism are prone to severe gestational hypertiglyceridemia [7]. In most cases of gestational hypertriglyceridemia reported in the literature, TPE was not initiated in the absence of pancreatitis [4][5][6][7][8][9] despite the established association of pancreatitis with life-threatening fetal complications and increased maternal mortality [12].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these phenomena result in an increase in VLDL production coupled with reduced triglyceride clearance, leading to a net increase in serum triglyceride levels [23]. In normal individuals this increase is modest, but in those who have deficiencies in lipoprotein lipase or apoprotein C-II (i.e., familial hyperlipidemia syndromes I, IV, and V), this increased VLDL synthesis can not be controlled and the result is severe hypertriglyceridemia [7]. TPE results in rapid reductions in triglyceride levels and offers a safe and feasible option for management of hypertriglyceridemia during pregnancy, when avoidance of fibrates is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Auch hier kann aber Schmerzfreiheit erst nach deutlich mehr als 24 h erwartet werden [3], was im Spezialfall der Schwangeren ein zu langer Zeitraum sein kann. Weitere Autoren beschreiben das Verfahren der Plasmapherese als therapeutische Intervention bei hypertriglyzeridämieinduzierter Pankreatitis [2,6]. Die Plasmapherese eignet sich zur raschen und effektiven Senkung der Triglyzeride, und es wird über Beschwerdefreiheit der behandelten Patienten innerhalb weniger Stunden berichtet [2].…”
Section: Verlaufunclassified
“…In this study, the average level of triglyceride was reduced by one third after the first plasmapheresis. Saravanan et al showed that the level of triglyceride was reduced by 73 and 82 %, respectively, after the second plasmapheresis [2]. As for the timing of plasmapheresis, the results were different in the literatures [3].…”
mentioning
confidence: 97%